Synergism With ε-Polylysine Hydrochloride and Cinnamon Essential Oil Against Dual-Species Biofilms of Listeria monocytogenes and Pseudomonas lundensis - Zhu, Junli; Liu, Jingcong; Hong, Xiaoli; Sun, Yang (Frontiers in Microbiology, 2022)
Various pathogenic and spoilage bacteria frequently co-exist in meat processing environments, and can form multispecies biofilms, causing significant health and economic issues. Despite the prevalence and co-existence, only little is known about possible interactions between Listeria monocytogenes and spoilers like Pseudomonas species, and their community-wide resistance against natural preservatives. This study evaluates the interactions between mono- or dual-species biofilms formed by L. monocytogenes (LM) and Pseudomonas lundensis (PL), as well as the sensitivity of these bacteria in dual-species biofilms to ε-polylysine hydrochloride (ε-PLH) alone or combined with cinnamon essential oil (CEO). The results showed that the biofilm cell density of P. lundensis in dual-species was higher (P<0.05) than L. monocytogenes, constituting about 85% of the total population. More biofilms and exopolysaccharide both in mono- or dual-species of the two psychrotrophic strains were greatly produced at 15°C than at 30°C. The biomass, bio-volume, and thickness of dual-species biofilms were significantly lower than single P. lundensis biofilm when tested using crystal violet staining, confocal laser scanning microscopy and scanning electron microscopy, indicating the competitive interactions between them prevail. Additionally, ε-PLH significantly reduced the biofilm development as mono- and dual-species in a concentration-dependent manner, especially single L. monocytogenes biofilm, which was consistent with the decrease of autoinductor-2 (AI-2) activity. L. monocytogenes as dual-species biofilms exhibited lower sensitivity to ε-PLH than its mono-biofilm probably due to protective effect conferred by P. lundensis. ε-PLH in combination with CEO, at the maximum sublethal concentrations (MSCs), showed enhanced the inhibitory activity against dual-species biofilm formation, as evidenced by thin spare spatial structures and reduced AI-2 activity. In addition, the preformed dual-biofilms were dramatically eradicated following treatment with ε-PLH combined with CEO at higher than minimum inhibitory concentration in comparison with either of the compounds used alone, indicating the synergistic antibiofilm of the two preservatives. The present study reveals the competitive interactions between the two strains in dual-species biofilms, in which the dominate P. lundensis significantly contributed towards the tolerance of L. monocytogenes to ε-PLH, and the use of combined preservatives shows it is an effective strategy to control the multispecies biofilms in meat processing.